Updating the landmark literature for the practice of geriatrics: Notable articles from 2012–2019. Issue 3 (25th January 2022) - Solberg, Laurence M.; Sehgal, Mandi; Patel, Pragnesh; Akers, Katherine G.; Pomputius, Ariel; Schwartz, Andrea; Scheiner, Shellina R.; Small, Alexander; Hidlebaugh, Elizabeth; Johnson, Theodore M.; Vaughan, Camille P.
Abstract: Background: Remaining current on the latest advances in the peer‐reviewed literature is a basic tenant of medical education and evidence‐based practice. We updated an important prior publication (Vaughan, et al.) identifying landmark articles in geriatric medicine by considering the influence of altmetrics and updating the list with notable articles published between 2012 and 2019. Methods: Articles were identified by searching Web of Science and Scopus for highly cited articles clinically relevant to geriatrics or gerontology and by searching the Altmetric Explorer database for relevant articles with high altmetric scores. The results of the literature search were screened and evaluated using a bibliometric score consisting of an adjusted journal impact factor, citation count, and altmetric score. Results: The top 12 notable articles in geriatrics were selected by a consensus panel and ranked using an expert opinion survey. This process reinforces the concept of combining subjective and objective measures to identify notable articles to be used for the education of healthcare professionals in geriatrics principles of care for older adults. Conclusions: While our update was performed approximately 9 years after the initial identification of landmark articles, we propose that future updates are conducted at an interval of every 5 years by the governance of a national professional society.